EXPLORING SPEAKING STRATEGIES EMPLOYED BY INDONESIAN EFL TERTIARY STUDENTS - Prabawa, Wawa Puja (Universitas Negeri Medan, 2018)
ABSTRACTThis study is a descriptive research since its purpose is to describe the Indonesian EFL tertiary students™ learning strategies in learning speaking English. The result of the study revealed that some speaking strategies are employed in terms of speaking English and improve speaking ability, namely cognitive, metacognitive and compensation strategy. In the type of speaking strategy that mostly employed by the students in terms of speaking English is compensation strategy, while cognitive strategy was indicated as the mostly speaking strategies employed by the Indonesian EFL tertiary students in improving their speaking ability. Keywords: Speaking, Strategy, Speaking Strategy, Tertiary Students